The Influence of Capital Structure, Operational Costs, and Liquidity on Profitability of Indonesian Commercial Banks During 2019–2023 - Mico Dharmawan; Pujiarti Pujiarti (Komunitas Dosen Indonesia, 2025)
Profitability is a company's ability to generate profit or income from its operational activities over a certain period. This indicator reflects the efficiency of a company in managing assets, capital, and costs to generate revenue. In Indonesia's banking sector, profitability plays a crucial role as the banking function serves as the backbone of the economy. This study aims to analyze the influence of independent variables, namely Capital Structure, Operational Costs, and Liquidity, on the dependent variable, Profitability, in National Commercial Banks listed on the Indonesia Stock Exchange during the 2019-2023 period. The population in this study consists of 15 companies, while the sample includes 6 companies. Based on the coefficient of determination test (R²), the Adjusted R Square value is 0.513 or 51.3%. Meanwhile, the remaining 49.7% is influenced by other variables. The partial test results for the capital structure variable show a significance value of 0.124 > 0.05 and a t-value of -1.588 < 2.056 (t-table). These results indicate that the capital structure variable does not influence profitability. The partial test results for the operational cost variable show a significance value of 0.00 < 0.05 and a t-value of -5.176 < 2.056 (t-table). These result indicate a negative and significant influence of the operational cost variable and profitability. The partial test results for the liquidity variable show a significant value of 0.00 < 0. ond a t-value of 4.244 > 2.056 (t-table). These results indicate a positive and significant influence of liquidity on profitability. Furthermore, the F-test results show a significance value of 0.00 < 0.05 and an F-value of 11.195 > 2.981 (F-table). Based on these F-test results, the independent variables (capital structure, operational costs, and liquidity) simultaneously influence the dependent variable (profitability).